AB1303 Ability of ultrasound in B mode and PD (PDUS) to detect erosions in mechanically strained area in healthy individuals (HI) and rheumatoid arthritis (RA): Comparison with micro computed tomography scan (μCT). (23rd January 2014) - Finzel, S.; Aergeter, P.; Schett, G.; D'Agostino, M.-A.
Abstract : Background: Both clinical studies and practice require exact detection of bone erosions in RA patients. Yet especially in mechanically strained areas such as the wrist (WR) and the metatarsophalangeal joints (MTPJ) there are certain limitations: acoustic window due to sesamoids and osteophytes, anatomical pitfalls (physiological vessel channels, grooves, and normal irregularities). Thus, there is a need for further PDUS studies on standardization. Objectives: To evaluate by PDUS physiological cortical breaks of mechanically strained areas in HI and to investigate whether their localization correlates with erosive lesions in RA patients. Methods: The WR of both hands of 43 and the MTPJ of 17 HI (without history of inflammatory joint disease) as well the WR of 38 and the MTPJ of 20 RA patients were examined by PDUS at volar, dorsal and, where possible, lateral side. Width and depth in all joint facets were assessed longitudinally and transversally. For PDUS an ESAOTE MyLab 70 (Genoa Italy) was used. Cortical break was defined as a defect in cortical lining detectable in 2 perpendicular planes (1). Physiological and abnormal breaks were defined according to the examiner. WR of the clinically more affected hands of 27 RA patients and of the dominant hands of 20 HI were scanned in μCT. MTPJ were not assessed in μCT. Prevalence, sensitivity and specificity of breaks in PDUS and μCT were recorded and compared. Results: 86 WR and 68 MTPJ were scanned by PDUS in HI, and 76 WR and 80 MTPJ in RA. 68 WR in RA were also assessed by μCT. 210 breaks out of 1290 performed scans were detected in WR of HI (16%); 94% were considered physiological and mostly detected in the dorsal scaphoid (13%), whereas the abnormal breaks were found in the lateral radius (38%). In the WR of RA, 262 breaks of 1135 scans (23%) were detected, 48% physiological and 52% pathological (both in the dorsal radius). In MTPJ of HI 45/478 breaks (9%) were found, 87% physiological (28% lateral MTP1) and 13% abnormal (66% dorsal MTP1). In MTPJ of RA 61/523 breaks (12%) were found, 13% physiological and 87% pathological (58% lateral MTP5). Table 1 shows mean (mm) cortical abnormal breaks by PDUS and μCT in HI and RA. All physiological breaks were considered vessel channels. Agreement among PDUS and μCT was excellent regarding specificity of detection of physiological and abnormal breaks in WR of HI and RA (0.94 and 0.99 in HI, 0.9 and 0.94 in RA respectively). Conclusions: In mechanically strained joints such as WR and MTPJ PDUS allows exact detection and discrimination between bone erosions and physiological breaks in cortical bone. Both US and μCT could identify predilection sides for nutritive vessels. References: Wakefield RJ et al. Musculoskeletal ultrasound including definitions for ultrasonographic pathology. J Rheumatol. 2005 Dec;32(12):2485-7. Disclosure of Interest: None Declared